На шляху національного відродження: релігійна складова духовного світу України кінця ХХ – початку ХХІ століть - Міщенко, Марина Миколаївна (НТУ "ХПІ", 2014)
У статті пропонується аналіз релігійної складової суспільного життя українців на рубежі ХХ–ХХІ ст. Акцентується увага на процесах секуляризації та їх негативних наслідках, особливо в сфері духовності та моралі. На зміну християнським нормам, які співзвучні з загальнолюдськими цінностями, приходять категорії користі, практицизму та індивідуалізації. Актуалізація дослідження даних питань пов’язана з потребою національного духовного відродження України та залученням тих духовних засад, що тисячоліття слугували фундаментом української духовності та культури. Національне відродження передбачає звернення до кращих зразків духовності і моральності, традицій і обрядів, витоки яких сягають християнської історії Київської Русі.

This paper presents the analysis of the religious component of Ukraini an social life at the turn of the XXI century. The author focuses her attention on the processes of ecularization and its negative consequences, especially in the field of spirituality and morality. The consequences of this situation are examined with a pa rticular focus on the fact that the categories of benefit, practicality and individualization replace the Christian norms that are consonant with human values. Actualization of the study of risen questions is connected with the needs of national spiritual revival of Ukraine and the involvement of the spiritual principles that served as the foundation of the Ukrainian spirituality and culture in the course of millennium. National revival provides for an appeal to the best examples of spirituality and morality, traditions and rituals, the origins of which date back to the Christian history of Kievan Rus.
Towards national revival: religious constituent of the spiritual world of Ukraine in the late 20th and early 21st centuries
Keywords: церква; секуляризація; духовність; культура; етика; religion; church; secularization; spirituality; culture; ethics; national revival